The impact of Greek labour market regulation on temporary and family employment: Evidence from a new survey - Achilleas Anagnostopoulos; W. Stanley Siebert (Institute for the Study of Labor (IZA), 2012)
This paper uses an original dataset for 206 workplaces in Thessaly (Greece), to study consequences of Greece's employment protection law (EPL) and national wage minimum for temporary employment. We find higher temporary employment rates especially among a grey market group of workplaces that pay low wages and avoid the national wage minimum. A similar factor boosts family employment. We also find that EPL matters, in particular, managers who prefer temporary contracts because temps are less protected definitely employ more temps. We discuss whether temporary and family work is a form of escape from regulation for less prosperous firms.
urn:nbn:de:101:1-201208096157
Keywords: J38; J41; J81; 330; temporary work; Greece; employment protection; national wage agreements; Arbeitnehmerschutz; Mindestlohn; Wirkungsanalyse; Befristeter Arbeitsvertrag; Familienunternehmen; Griechenland